Hepatitis B and C viral markers in patients with sickle cell disease in Ibadan, Nigeria (2003)
Serum samples from 180 Sickle Cell Disease (SCD) patients attending Medical Out patients (MOP) clinic of the Department of Haematology, UCH, Ibadan, Nigeria were tested for the presence of HbsAg and anti-HCV in their blood samples. The result showed that HBV infection was slightly higher (not significant) than HCV infection among SCD patients (P>0.05). In addition, the result showed that the mean number of transfusion was higher among patients who were sero-positive for both HbsAg (5.0 +/- 6.6) and anti-HCV (4.6 +/- 6.7) when compared to patients who were negative for both viruses (2.7 +/- 3.0 and 2.9 +/- 3.2) for HBsAg and anti-HCV respectively. These observations is an indication that there is an urgent need to screen blood units for hepatitis B and C virus infections prior to transfusion in order to reduce HCV infection among SCD patients in Nigeria. Furthermore, it suggests the need to vaccinate SCD patients against HBV in this environment.